Deciphering the genome repertoire of Pseudomonas sp. M1 toward β-Myrcene biotransformation - Castro, Pedro Miguel Soares (2015)
Pseudomonas sp. M1 is able to mineralize several unusual substrates of natural and xenobiotic origin, contributing to its competence to thrive in different ecological niches. In this work, the genome of M1 strain was resequenced by Illumina MiSeq to refine the quality of a published draft by resolving the majority of repeat-rich regions. In silico genome analysis led to the prediction of metabolic pathways involved in biotransformation of several unusual substrates (e.g., plant-derived volatiles), providing clues on the genomic complement required for such biodegrading/biotransformation functionalities. Pseudomonas sp. M1 exhibits a particular sensory and biotransformation/biocatalysis potential toward β-myrcene, a terpene vastly used in industries worldwide. Therefore, the genomic responsiveness of M1 strain toward β-myrcene was investigated, using an RNA sequencing approach. M1 cells challenged with β-myrcene(compared with cells grown in lactate) undergo an extensive alteration of the transcriptome expression profile, including 1,873 genes evidencing at least 1.5-fold of altered expression (627 upregulated and 1,246 downregulated), toward β-myrcene-imposed molecular adaptation and cellular specialization. A thorough data analysis identified a novel 28-kb genomic island, whose expression was strongly stimulated in β-myrcene-supplemented medium, that is essential for β-myrcene catabolism. This island includes β-myrcene-induced genes whose products are putatively involved in 1) substrate sensing, 2) gene expression regulation, and 3) β-myrcene oxidation and bioconversion of β-myrcene derivatives into central metabolism intermediates. In general, this locus does not show high homology with sequences available in databases and seems to have evolved through the assembly of several functional blocks acquired from different bacteria, probably, at different evolutionary stages.